Helminth communities of Leptodactylus latrans (Anura: Leptodactylidae) from the Atlantic rainforest, south-eastern Brazil - Toledo, G. M. [UNESP]; Morais, D. H. [UNESP]; Silva, R. J. [UNESP]; Anjos, L. A. [UNESP] (Cambridge Univ Press, 2015)
The helminth fauna associated with Leptodactylus latrans, a large frog living in a disturbed environment of Atlantic rainforest in south-eastern Brazil, was evaluated. We found eight helminth taxa, including five nematode species, Falcaustra mascula, Oswaldocruzia subauricularis, Physaloptera sp., Rhabdias sp. and an unidentified cosmocercid, two trematodes, Gorgoderina parvicava and Haematoloechus fuelleborni, and one larval cestode. The overall prevalence of infection was 63.2% with a mean intensity of 11.3 +/- 3.8. The cosmocercid nematode and O. subauricularis showed the highest prevalences, although the trematode G. parvicava was the most abundant and dominant parasite species. Host size positively influenced both the intensity of infection and parasite species richness. Our data suggest that the juvenile individuals of L. latrans are more susceptible to parasitic infection than the adults. The comparison of the similarity of this community component with that found in other studies in South America shows that, as well as the characteristics of the host, the sampling area also influences the parasitic fauna. Therefore, the results of this study agree that the helminth communities of frogs have relatively low species richness and dominance of generalist species.